A Cultural-History Analysis on Malay-Islamic Heritage of Siak Sri Indrapura through the Historical Urban Landscape Approach in Pekanbaru City - Muhammad Rasyidul Ilmi; Regan Leonardus Kaswanto; Nurhayati HS Arifin (UIN Sumatera Utara Medan, 2022)
The Sultanate of Siak Sri Indrapura plays a vital role in the history of the development of Islam and Malay culture in Pekanbaru City. Pekanbaru City is a cultural-historical tourist attraction through the Malay-Islamic landscape, which can be seen from its historical heritage. The historical heritage is a Malay-Islamic cultural heritage building that still exists today. This study will explain the analysis of cultural history and its preservation management. The method used is qualitative with a Historic Urban Landscape (HUL) approach. The study's results showed 16 cultural heritage sites with varying levels of management, five sites in very well-maintained condition, three well maintained, and eight poorly maintained. Several challenges are faced: damaged buildings, incomplete historical data, regulations, and the absence of tourist programs. In addition, the distance between cultural heritage and the enthusiasm of the Malay community is a potential that needs to be optimized. The vision is to make Pekanbaru City the center of Malay-Islamic identity based on the waterfront city through the concept of preservation. The proposed preservation management is a historical tourism development program to connect cultural heritage buildings based on tourist trails that prioritize cultural and historical interpretation effectiveness and efficiency.